Peningkatan Peningkatan Pemahaman Fiqih Ibadah Melalui Kajian Kitab Safinatunnajah di Majelis Ta'lim Arofah Dusun Karang Desa Prajegan - Nur Diansyah; Suci Midsyahri Azizah; Kadenun Kadenun (Social Science Academic, 2025)
The taklim assembly is a place of religious learning that has a great influence on the religious development of the community, the taklim assembly is present in the midst of society with the hope of being able to make a positive contribution to its congregation. This study aims to determine the increase in understanding of the figh of worship through the study of the Safinatunnajah book at the Arofah Ta'lim Assembly in Karang Hamlet, Prajegan Village. The research method used is qualitative with an ABCD approach with existing asset developers. Data collection techniques are done through observation, interviews, and documentation. The results showed that the study of Safinatunnajah book in Majelis Ta'lim Arofah Karang Hamlet, Prajegan Village has increased the understanding of the congregation about the figh of worship. The increase in understanding can be seen from several indicators, namely: Increased knowledge of jama'ah about the pillars, conditions, and sunnah of worship. The increasing ability of the congregation in performing worship correctly and according to Islamic law. Increased awareness of the importance of performing worship solemnly and sincerely. Increased motivation of the congregation to learn more about the figh of worship. This increased understanding of figh of worship is influenced by several factors, namely: teaching methods used by the ustadz, study materials that are easy to understand, and a conducive learning atmosphere. This research recommends that Majelis Ta'lim Arofah Karang Hamlet, Prajegan Village, continue to improve the quality of its teaching.